Different conceptions of Jewish and palestinian Nationhood: the question of palestine viewed through ethnic, religious and political identities in conflict - Çoban, Melih (My University, 2003)
ilistin sorunu geçtiğimiz yüzyıl boyunca uluslararası ilişkilerin önemli bir konusu olmuş ve hala sorunun taraflarınca kalıcı ve yapıcı bir çözüm sağlanamamıştır. Bir toprak meselesi olarak ortaya çıkışını takiben Filistin sorunu, Yahudi ve Filistin taraflarının yüzleştikleri karşıtlarının farklı etnik köken, kültür ve dinin mensubu olmalarını kavramasıyla derinleşmiştir. Birbirlerine karşı verdikleri mücadele içinde tutundukları etnik, dini ve siyasi kimlikler, Yahudilerin ve Filistinlilerin bölgede varolma stratejilerini derinden etkilemiştir. Buna ek olarak, bu varoluş mücadelesi süresince, her iki taraf soruna farklı perspektiflerden yaklaşan çeşitli siyasi kimlikler geliştirmiştir. Böylece, süreç boyunca, Filistin sorunu Yahudi ve Filistinlilerin etnik, dini ve siyasi kimliklerini kavrama ve sürdürme biçimiyle iç içe seyretmiştir. İsrail Yahudi toplumu etnik olarak Aşkenazi ve Sefardim diye iki ayrı gruba ayrılırken, bu iki grup arasındaki sosyo-kültürel ve siyasi çatışmalar tarafların Filistin sorununa farklı bakışları itibariyle sorunun derinleşmesine neden olmuştur. Benzer şekilde Yahudilerin farklı dini ve siyasi kimlikleri de Yahudi toplumu içinde Filistin sorununun farklı kavranışlarına yol açmıştır. Filistin tarafında ise, Filistin toplumunun maruz kaldığı topraksal, dini ve siyasi bölünmüşlükler Filistin milliyetçiliğinin gelişimi ve Filistin kurtuluş davasının seyrini etkilemiş ve Filistin toplumu içinde gelişen alt kimlikler sorunun ve İsraillilerin farklı kavranışlarına yol açmıştır. İsrail' de yaşayan Çerkez, Dürzi ve Bedevi toplumları da, Filistin meselesinde çıkarları doğrultusunda İsrail' in yanında yer almıştır. Filistin sorunu toprak paylaşımı ve siyasi meşruiyet mücadelesinin yanı sıra Filistinli ve Yahudi kimliklerinin çatışma sürecini içermiştir. Bu süreç boyunca iki toplum içinde farklı alt kimliklerin gelişimi de sorunun farklı perspektiflerde kavraması ve tepki göstermesi şeklinde katkıda bulunmuştur. The question of Palestine has been a significant subject of international relations during the past century and yet, a permanent and constructive solution has not been achieved by the parties to the question. Following its emergence as a territorial issue, the question of Palestine has been deepened as both the Jewish and Palestinian parties realized that the opponents they were facing were people of different ethnicities, cultures and religions. Jews and Palestinians based their strategies of survival in the region on these identity factors, whereby they sought to preserve their ethnic and religious identities of their own to ensure mobilization among their communities while confronting with the other side. In addition, during this search for survival, both sides developed various political identities, each approaching the issue from a different perspective. Thus, during the process, the question of Palestine has evolved in accordance with the perceptions of Jewish and Palestinian identities on ethnic, religious and political dimensions. While Israeli Jews are ethnically divided into two groups as the Ashkenazim and Sephardim, the socio-cultural and political conflicts between these two has led to the deeping of the question of Paletsine. Similarly, different religious and political identities among the Jews has led to the same effect. On the Palestinian side, the territorial, religious and political dispersions the Palestinians faced have influenced the development of Palestinian nationalism and led to the perception of the question of Palestine by these various sub-identity groups. The Circassian, Druze and Bedouin communities living in Israel have taken part at the side of the Israelis due to their interests. The question of Palestine, in addition to land sharing and political legitimacy, has also involved the process of conflict between Jewish and Palestinian identities. During this process, the development of different sub-identities within both communities has affected the question in terms of the parties perceiving and responding to it in different perspectives.
Keywords: Filistin Sorunu; Filistin ve İsrail; Ortadoğu; Tarih